Years of life lost by COVID-19 in Portugal and comparison with other European countries in 2020 - André Vieira; Vasco Peixoto Ricoca; Pedro Aguiar; Paulo Sousa; Carla Nunes; Alexandre Abrantes (BMC Public Health, 2021)
Abstract Background The impact of the COVID-19 pandemic has been measured in different metrics, mostly by counting deaths and its impact on health services. Few studies have attempted to calculate years of life lost (YLL) to COVID-19 and compare it with YLL due to other causes in different countries. Methods We calculated YLL to COVID-19 from week10 to week52 in 2020 for eight European countries by methods defined by the WHO. We calculated excess YLL by subtracting the average YLL from 2017 to 2019 to the YLL in 2020. Our analysis compared YLL to COVID-19 and the excess YLL of non-COVID-19 causes across countries in Europe. Results Portugal registered 394,573 cases and 6619 deaths due to COVID-19, accounting for 25,395 YLL in just 10 months. COVID-19 was responsible for 6.7% of all deaths but accounted for only 4.2% of all YLL. We estimate that Portugal experienced an excess of 35,510 YLL (+ 6.2%), of which 72% would have been due to COVID-19 and 28% due to non-COVID-19 causes. Spain, Portugal, and the Netherlands experienced excess YLL to non-COVID-19 causes. We also estimated that Portugal experienced an excess of 10,115 YLL due to cancer (3805), cardiovascular diseases (786) and diseases of the respiratory system (525). Conclusion COVID-19 has had a major impact on mortality rates in Portugal, as well as in other European countries. The relative impact of COVID-19 on the number of deaths has been greater than on the number of YLL, because COVID-19 deaths occur mostly in advanced ages.